Laboratory and field evaluation of cement grouted bituminous mixes. Issue 6 (17th August 2020) - Bharath, G.; Shukla, Manoj; Nagabushana, M. N.; Chandra, Satish; Shaw, Amit
Abstract : Cement Grouted Bituminous Mix (CGBM) is a composite material, in which air voids present in the bituminous mix are grouted with a cementitious material. The main aim of this study is to develop and evaluate CGBM in the laboratory and field. A conventional dense graded Bituminous Concrete (BC) mix is also considered for comparison. This paper presents the details of different investigations carried out for evaluation of CGBM mix for properties such as Indirect Tensile Strength (ITS), Resilient Modulus and Dynamic Modulus at different temperatures. Performance characteristics such as rutting, fracture energy, moisture resistance, oil spillage and durability were also evaluated for the mixes. A CGBM test section has been laid on site and is being monitored for its performance. Results show that CGBM has better ITS, Resilient Modulus, Dynamic Modulus, and Rutting performance than a conventional bituminous mix. It shows a slight reduction in durability and crack resistance due to the relative brittleness of the hardened cement constituent but within acceptable limits. The material is also more resistant to damage by moisture and diesel. CGBM mixes are less temperature susceptible compared to conventional bituminous mix. Dynamic Modulus and Phase Angle master curves for CGBM mixes have been developed in the study. Full depth grouting was observed in field core samples and Micro Computed Tomography (Micro-CT) tests were carried out to check the air voids connectivity and their content in the CGBM mix.